Hubungan Indeks Massa Tubuh Terhadap VO2 Max Pada Pemain Sepak Bola Laki-laki Amatir - Ajeng Nila Andini (2021)
An important component in the game of football is anthropometry and physical conditions. Physical conditions include speed, endurance, agility, and power. Endurance is divided into two, namely anaerobic endurance (muscle strength) and aerobic endurance (cardiorespiratory). Measurement of aerobic endurance (cardiorespiratory) is done by measuring the maximum oxygen volume (VO2 Max). In a soccer game, every player must have a good VO2 Max. Because normal football matches are played for 90 minutes with a break of 15 to 20 minutes. This study used a cross-sectional study method with 24 male respondents aged 20-27 years. Measurement of BMI using the formula BMI = Body Weight (kg) / Height (m)2. Then the measurement of VO2 Max using a 12-minute running test/cooper test with the formula (Distance traveled in meters - 504.9) / 44.73. The results from 24 respondents that the highest BMI value is ideal with a percentage of 66.7% and the highest VO2 Max value is very good and good with a percentage of 29.2%. After the correlation test, it was found that there was a relationship between BMI and VO2 Max, and the correlation coefficient of -0.609 was negative or not in the same direction. The conclusion of this study is that with increasing BMI there is a decrease in VO2 Max, which indicates that increasing BMI causes a decrease in cardiorespiratory fitness.